Understanding the saving behavior of poor households: evidence from Egypt - Helmy, Imane Abdel Fattah (AUC Knowledge Fountain, 2015)
Given that there is a recent growing interest in mobilizing savings of poor households, this study investigates the factors that affect household saving in Egypt using a probit model. It uses data of the Egypt Labor Market Panel Survey (ELMPS) carried out in 2012. Also, it tests the impact of accessing credit on informal and formal saving. The results of the study show that the determinants of informal saving are quite different from formal saving. For example, access to credit significantly increases the probability of saving among the poor. However, credit increases informal saving while it has an insignificant effect on formal saving. This suggests that there is little evidence on the mutually reinforcing relationship between formal borrowing and formal saving since there is a weak incentive to convert informal savings of the poor into formal deposits. Females have higher tendency to save, yet they save informally which highlights the need for gender-sensitive saving products. Also, health emergencies have a significant negative effect on informal saving of poor households while insurance reduces the use of savings as Out Of Pocket (OOP) expenditures on health. Therefore, policies in Egypt should develop an inclusive financial system that increases awareness and confidence in the financial market and improves access to financial services.